Cardio-renal Protective Role of Alpha Lipoic Acid Against Mesterolone in Relation to ANP, Nrf2 and TSPO genes - Mohammed Hayder Asker; Tahani S.S. Al-Azawi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The protective role of Alpha Lipoicacide on cardio_renal function in rabbits subjected to Mesterolone wasstudied. A total of twenty adult female rabbits was divided into fourgroups:Control,Mesterolone(0.65mg/kg B.w),Lipoic acid(10 mg/kg B.w) and Mesterolone +Lipoic acid.All animals received treatment everyday for 60 days by oral administration during the period from 1stAugust 2018 to 1st June 2019. At theend of the experiment, animals were anesthetized by double dose anesthesia, heart and kidney tissues forRNA isolation were taken.This retrospective study was carried out in Department of physiology/College ofVeterinary Medicine/University of Baghdad/Iraq. The heart and kidney tissue were isolated for the expressionof atrial natriuretic peptide,nuclear factor erythroid 2 related factor 2 and Translocator protein genes.Theresults showed a significant increase in the expression of the genes in Mesterolonegroup.Whereas, Lipoicavid supplementation decreases them. These results indicate the important effect of Alpha lipoic acid oncardiorenal function. These anabolic androgenic steroids such as Mesterolone exert an up regulation of atrialnatriuretic peptide,nuclear factor erythroid 2 related factor 2 and Translocator protein genes expression toovercome the damage of heart and kidney tissue induced by them.